2017
DOI: 10.1177/0884533617722929
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Implications for Long‐Term Survivors of Pancreatic Cancer Surgery

Abstract: With slowly increasing survival rates in pancreatic cancer and international consensus guidelines recommending surgical resection of premalignant lesions, survival post-pancreatic resection is increasing. With longer survival time, the significant comorbidities of such major surgery have far-reaching effects on the nutrition status of the survivor of pancreatic cancer. This review describes the many nutrition-related side effects of pancreatic surgery, including the development of pancreatic enzyme insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 66 publications
(210 reference statements)
0
39
0
2
Order By: Relevance
“…Therefore, it has been postulated that patients after pancreaticoduodenectomy (PD) might show deficiencies in several micronutrients including fat-soluble vitamins D and E, selenium and iron, independent of dietary intake or of pancreatic exocrine function, and therefore clinical recommendations for micronutrient evaluation have been issued 9 , 10 . But long-term data concerning the time course of micronutrient levels after cancer-related pancreatic head resection are missing 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been postulated that patients after pancreaticoduodenectomy (PD) might show deficiencies in several micronutrients including fat-soluble vitamins D and E, selenium and iron, independent of dietary intake or of pancreatic exocrine function, and therefore clinical recommendations for micronutrient evaluation have been issued 9 , 10 . But long-term data concerning the time course of micronutrient levels after cancer-related pancreatic head resection are missing 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A reduced number of patients develop NAFLD in the treatment group vs historical controls [54]. Still, studies have not shown whether stopping enzyme supplementation leads to a refractory appearance of fatty liver [50]. It should be noted that not all patients receiving pancreatic enzyme supplementation were protected from NAFLD, and spontaneous NAFLD regression was observed in patients without treatment.…”
Section: Nafld Following Pancreatoduodenectomymentioning
confidence: 99%
“…The underlying pancreatic disease, the surgical procedure performed, and the extent of tissue loss are prognostic factors for the development of EPI. EPI is reported in 50-100% of oncological patients' post-PD as opposed to 0-42% in distal pancreatectomy [50]. Pancreatic head cancer is a constant risk factor for de novo post-PD NAFLD, and it is conceivable that it is due to a small and atrophic remnant pancreas following surgery, which increases the risk of EPI exponentially [45].…”
Section: Nafld Following Pancreatoduodenectomymentioning
confidence: 99%
See 1 more Smart Citation
“…The reported rate of major post‐operative complications and 30‐day mortality is as high as 40% and 9%, respectively . In addition, many patients suffer long‐term complications associated with pancreatectomies, including diabetes, pancreatic exocrine insufficiency, malnutrition and gastrointestinal motility disorders . It is therefore essential that pancreatic resections are offered to patients with satisfactory pre‐morbid status who receive appropriate counselling and support prior to and following their pancreatectomy.…”
Section: Introductionmentioning
confidence: 99%